The transmission of monetary shocks in the euro area: a V AR analysis based on euro-wide data - Kakes, Jan; Pattanaik, Sitikantha (PSL Quarterly Review, 2013)
Using area-wide data, we simulate the responses of inflation and real output following monetary shocks in the EMU. We find that short-term interest rate shocks have a significant impact on real activity, but hardly on prices. M3 shows a perverse short-term response to a monetary contraction, which should be taken into account when interpreting the reference value of money growth (the "first pillar" of the Eurosystem's monetary strategy). Shocks to the effective exchange rate have a rapid impact on prices, money growth and real activity. As the exchange rate itself is hardly affected by monetary policy shocks, though, there is little scope for an exchange rate policy. Rather, these findings underscore the important role that the exchange rate should play as an information variable within the "second pillar" of the monetary strategy. JEL Codes: N1, E52, F36